Nonlinear stability and optimization of thin nanocomposite multilayer organic solar cell using Bees Algorithm - Dat, Ngo Dinh; Anh, Vu Minh; Quan, Tran Quoc; Duc, Pham Truong; Duc, Nguyen Dinh (Thin-walled structures, 2020)
This paper carries out the nonlinear stability of nanocomposite multilayer organic solar cell (NMOSC) subjected to axial compressive loads. The model of organic solar cell is assumed to consist five layers: Al, P3HT:PCBM, PEDOT:PSS, IOT and Glass. Based on the classical plate theory, the basic equations are established taking into account the effect of elastic foundations and initial imperfection. The approximation solutions are selected based on the boundary conditions of the four edges of NMOSC. The equation which indicates the relationship between axial compressive loads and deflection amplitude of NMOSC is obtained by using the Galerkin method. Bees Algorithm is applied to maximize the value of critical buckling load with nine variables including the thickness of five layers, the length and the width of NMOSC and two stiffness coefficients of elastic foundations. The numerical results show the effect of geometrical and material parameters, initial imperfection and elastic foundations on the nonlinear static stability and the critical buckling load of NMOSC. Optimal values of nine geometrical parameters of NMOSC are also determined. •The nonlinear stability of nanocomposite multilayer organic solar cell is investigated.•The classical plate theory is used to establish basic equations.•The effect of elastic foundations and initial imperfection are taken into account.•Effects of material and geometrical properties, elastic foundations and initial imperfection are discussed.•Bees Algorithm is used to determine the maximum value of critical buckling load depending on nine variables.